The Moderating Role of Digital Orientation on the Relationship between Corporate Innovation and Internationalization: Evidence among Malaysian Technology Companies - Hui-Wei, You; Rayenda Khresna, Brahmana (Universiti Malaysia Sarawak, 2022)
The aims of this research study are to examine the role of digital orientation on innovation and internationalization. This study was interested to examine the accuracy of agency theory, resource-based view theory and organization orientation theory. The other attributes this study used to investigate in this study are firm size, leverage, growth, asset effective, net profit margin, financial risk, firm age, and systematic risk. This study used panel regression such as the one-lagged regression model, GMM regression model, doubled cluster model, and logit model as a methodology in this study. The scope of study comprises the Malaysia public listed technology companies from electricity, electronic and equipment, general industrials, Industrial Engineering, Pharmaceuticals and Biotechnology, Software and computer service, support services, technology hardware and equipment, general retailers, personal goods, automobiles, and parts, beverages, chemicals, food produces, forestry and paper. Eight-year period are taken for the study from 2011 to 2018. Stata software version 14 is used to run the data. Using the robustness panel regression, this study found high innovation, high internationalization. This means that innovative technology companies often initiate their international business. Meanwhile, this study found that digital orientation does not help these companies to internationalize their sales due to financial constraints. In fact, these results show that digital orientation interacts with innovation to increase the internationalization asset. It was partially accepted. Adopting resource-based view theory, this theory suggests that the manager involved internationalization is positively related to both innovation and firm value, and principal conducted in digital orientation positively moderates the relationship between internationalization and innovation. The research findings contribute to the literature and deliver implications for international business and management on the relationship between innovation, and internationalization of Malaysia technology companies. First, this research suggested the moderating role of Digital orientation on the relationship between innovation, and Internationalization. Second, this study presents the unique contribution of a theoretical model specific to the context of digitalization and offer a base which other researcher may prove and develop through empirical research. Keywords: Digital orientation, innovation, internationalization strategy